178k views
1 vote
-8(x + 1) + 3(x - 2) = -3x + 2


User JagaSrik
by
4.3k points

1 Answer

4 votes

Answer:

x = -8

Explanation:

Step 1: Write equation

-8(x + 1) + 3(x - 2) = -3x + 2

Step 2: Solve for x

Distribute: -8x - 8 + 3x - 6 = -3x + 2

Combine like terms: -5x - 14 = -3x + 2

Add 5x to both sides: -14 = 2x + 2

Subtract 2 on both sides: -16 = 2x

Divide by 2 on both sides: -8 = x

Step 3: Check

Plug in x to verify correct solution.

-8(-8 + 1) + 3(-8 - 2) = -3(-8) + 2

-8(-7) + 3(-10) = -3(-8) + 2

56 - 30 = 24 + 2

26 = 26

User Herrbischoff
by
4.9k points